Kearifan Penjual dan Pembeli Produk Barang dan Jasa Berbahan Dasar Kapuk dalam Melakukan Transaksi Jual Beli di Desa Tegallinggah - Rochmatus Shoviy; Luh Indrayani (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
In general, trade transactions is a form of transaction that is often carried out by society. Trade transactions is defined as the exchanging goods for goods or goods for money betwen sellers and buyers which is carried out by agreement. On conventional or online trade transactions, the main goal that seller expectes is to maximize profit. Thus, some entrepreneurs cheat to get many profit. This is different from Tegallinggah community’s transaction in the cotton industry, they prioritize moral values. The most of sellers from cotton industry are Muslims, they believe that their activities in trade will be blesed. The aims of this study is to know the phenomeneon of local wisdom within trade transaction and to know the meaning of local wisdom phenomeneon. This is a qualitative research using phenomenological approach.